2017
DOI: 10.7554/elife.27402
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the biflavonoid hinokiflavone as a pre-mRNA splicing modulator that inhibits SENP

Abstract: We have identified the plant biflavonoid hinokiflavone as an inhibitor of splicing in vitro and modulator of alternative splicing in cells. Chemical synthesis confirms hinokiflavone is the active molecule. Hinokiflavone inhibits splicing in vitro by blocking spliceosome assembly, preventing formation of the B complex. Cells treated with hinokiflavone show altered subnuclear organization specifically of splicing factors required for A complex formation, which relocalize together with SUMO1 and SUMO2 into enlarg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…Second, glutamine-derived glutamate contributes to glutathione biosynthesis through facilitating the uptake of cystine via the xCT transporter. Third, glutamine contributes to the cellular redox balance by supporting NADPH production [25] [27]. SENP1 played an important role in regulating cancer development and progression in our study, These observations might be correlated with the ability of glutamine to better cope with stresses, especially oxidative stress.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Second, glutamine-derived glutamate contributes to glutathione biosynthesis through facilitating the uptake of cystine via the xCT transporter. Third, glutamine contributes to the cellular redox balance by supporting NADPH production [25] [27]. SENP1 played an important role in regulating cancer development and progression in our study, These observations might be correlated with the ability of glutamine to better cope with stresses, especially oxidative stress.…”
Section: Discussionmentioning
confidence: 54%
“…In-silico screening was used to search for small molecule inhibitors of SENP1 in conjunction with biochemical assays, and a new chemotype of small molecule inhibitors that noncovalently inhibit SENP1 was found and the inhibitory abilities of representative inhibitors of SENP1 in cells confirmed in HELA cells [26]. Hinokiflavone, which belongs to a subclass of the plant flavonoid family, could have a similar effect through its ability to block SENP1 activity and therefore stimulate the accumulation of hyper-SUMOylated proteins to inhibit cancer progression [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that apigenin and luteolin treatment induced the accumulation of bulk poly(A) + RNA, as well as the retention of intron-containing transcripts from target mini genes, in the nuclear speckles, implying that these flavonoids affect a broad range of mRNA splicing events. Our results from LC-MS/MS, docking studies and SF3B1 overexpression analysis simply suggest that these flavonoids interact with U2 and U5 snRNP, possibly through the interaction with SF3B1, to modulate mRNA splicing, although we cannot exclude other possible splicing regulatory mechanisms by these flavonoids, such as SUMOylation of spliceosomal components previously reported for an apigenin-and luteolin-related biflavonoid, hinokiflavone (Pawellek et al, 2017). Together, these findings suggest that apigenin and luteolin associate with spliceosomal components to directly prevent the function of spliceosomes, thus affecting alternative splicing at the genomewide level.…”
Section: Discussionmentioning
confidence: 56%
“…The daily intake of bioactive food compounds is expected to be effective for the prevention of chronic diseases. For example, polyphenols and carotenoids have antioxidant activity and function in preventing lifestyle-related diseases (Pandey and Rizvi, 2009;Reinisalo et al, 2015;Young and Lowe, 2001). Flavonoids, which are abundant in fruit and vegetables, have been reported to reduce the risk of lifestyle-related diseases and carcinogenesis (Bo et al, 2016;LĂł pez-lĂĄ zaro, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using SSA and PlaB, it was reported that SF3B1 is involved not only in the early splicing reaction by BP recognition but also in the exon-ligation reaction [172], suggesting additional roles for SF3B1 throughout the splicing process. The relationship between splicing factor and SUMOylation, a post-translational modification, was partially clarified by hinokiflavone, which is an analogue of isoginkgetin [173]. Previously, spliceosomal proteins were revealed as SUMO conjugation targets; however, little is known about the involvement of SUMO in spliceosome biogenesis and splicing regulation [174].…”
Section: Fr901464mentioning
confidence: 99%